RANCANGAN CITY BRANDING KOTA PADANG PENTINGNYA SEBUAH BRANDING DALAM PERKEMBANGAN KOTA - Haris Satria (Institut Seni Indonesia Yogyakarta, 2013)
The final work is titled Draft City Branding Padang city. The introduction has not been packagedproperly. It creates an image that is less attractive for tourists, when in fact the City The potential thatought to be proud of by the people. This design uses the theory of city branding, communication theory,design theory and the theory of color. Therefore, in the design of this time are highlighted in The laterthrough verbal and visual messages, tagline and media applications that are effective and efficient.As for media design is the logo along with the explanation. Design a billboard mediaapplications, facebook account, t-shirts, mugs, keychains, signed area, posters, pins, post card, sticker,calendar and jlaxchange. All the media is part of the process of city branding Padang city.Keywords: Concept, City Branding, Padang.